Efeito da densidade de ninfas de Aphis gossypii Glover, 1877 (Hemiptera, Aphididae) no consumo alimentar e aspectos biológicos de Orius insidiosus (Say, 1832) (Hemiptera, Anthocoridae) - Guedes, Ivone Vilar; De Bortoli, Sergio Antonio; Thuler, Robson Thomaz; Eudes de Moraes Oliveira, Jose; Vacari, Alessandra Marieli (My University, 2008)
Orius insidiosus (SAY, 1832) is an important predator for biological pest control programs. The objective of this work was to evaluate the functional response, predation capacity and reproductive aspects of O. insidiosus when predating 1, 5, 10, 15, and 20 third/fourth instar nymphs of Aphis gossypii. The tests were conducted under laboratory conditions. Females of the predator were individually maintained in Petri dishes with a cotton leaf at each one of the aphid densities. The average rate of predation was of 0.93 [plus or minus] 0.13, 3.58 [plus or minus] 0.80, 7.31 [plus or minus] 1.45, 7.40 [plus or minus] 1.16, and 10.54 [plus or minus] 1.84 at the densities of 1, 5, 10, 15, and 20 aphids, respectively. The results showed an attack rate of 0.10 h-1 and 1.82 h of manipulation time. The predator spent 3.10 to 4.08 h feeding on leaf cotton glands; this behavior was not directly influenced by the prey density. The proportion of egg laying per female grew up to the density of 10 nymphs whereas the number of eggs per laying increased with the number of available preys.
Biological aspects of Orius insidiosus (Say, 1832) (Hemiptera: Anthocoridae) feeding on Aphis gossypii (Glover, 1877) (Hemiptera: Aphididae).